2009
DOI: 10.1108/09653560910953207
|View full text |Cite
|
Sign up to set email alerts
|

Disaster management: findings from a systematic review

Abstract: PurposeThe paper aims to discuss a systematic review of the literature about disaster management within the period 1980‐2006.Design/methodology/approachThe research protocol is based on the methodology that is commonly used in healthcare for analysing the literature and provides a state‐of‐art medical discipline. The paper presents both a descriptive analysis and a thematic analysis in order to provide a state‐of‐art of international literature. The research protocol is provided in order to make transparent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(159 citation statements)
references
References 55 publications
(96 reference statements)
3
141
0
3
Order By: Relevance
“…(10)H management particularly in low-and middle-income country (LMIC) settings is hampered by the paucity of the evidence-base. (8,11) There are also considerable uncertainties with regards to how evidence-based practice is best achieved. Reviews from high-income countries have identified various determinants and barriers to developing evidence-based practice in disaster management such as knowledge management issues, system configuration issues and behavioural aspects.…”
Section: Introductionmentioning
confidence: 99%
“…(10)H management particularly in low-and middle-income country (LMIC) settings is hampered by the paucity of the evidence-base. (8,11) There are also considerable uncertainties with regards to how evidence-based practice is best achieved. Reviews from high-income countries have identified various determinants and barriers to developing evidence-based practice in disaster management such as knowledge management issues, system configuration issues and behavioural aspects.…”
Section: Introductionmentioning
confidence: 99%
“…19 This uses a systematic search methodology whilst allowing for the review of a broader, less restrictive, range of evidence. We anticipated that most of the evidence was likely to be short reports [14][15][16][17] . Consequently, we intentionally adopted a more inclusive approach to include papers that might have been excluded in a more rigid systematic review format as we wanted to capture the full range of health impacts associated with this type of disaster.…”
Section: Scoping Reviewmentioning
confidence: 99%
“…Many are confined to a specific geographic area 12,13 whilst others have cited the lack of available good quality evidence 10,11 , a common problem encountered in disaster management research [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Many have discussed the definition, the stages of the disaster management, the process, the plan, the involvement of people, the use of technology and information as well as theoretical framework to assist in disaster management plan. However, according to [26], the most popular topic selected for the research is on the disaster management phases and process.…”
Section: Approaches To Disaster Managementmentioning
confidence: 99%